The Transformation of Urban Space before and after the Greek Revolution: The Case of Mega Revma (Arnavutköy) - Ansel, Esra (Historein, 2023)
This article aims to uncover the links between the 1821 Greek Revolution and the transformation of the social topography and landscape in Mega Revma (Arnavutköy), a Bosphorus village with a large Greek Orthodox population. In the eyes of the sultan, the Phanariots were the ones who “misled the loyal Greek reaya to rebel against their rightful sovereign”. Thus, it is not surprising that Mega Revma, as a centre of Phanariot life, was a place transformed by the crisis of 1821. The processes of social and religious restructuring of Mega Revma took place in two main phases. While the first phase (1821–1828) consisted of more violent and immediate responses to the revolution, the second phase was a long process that aimed to Islamise the village using conciliatory measures and building projects.